Behaviour of metals in an urban river and the pollution of estuarine environment. (1st November 2019) - Wijesiri, Buddhi; Liu, An; He, Beibei; Yang, Bo; Zhao, Xu; Ayoko, Godwin; Goonetilleke, Ashantha
Abstract: The high pollutant loads discharged from cities pose risks to urban waterways, and in turn the estuarine environments, making it challenging to improve urban liveability. Past studies on the behaviour of pollutants in rivers have largely investigated their transport along the waterway, primarily focusing on the movement of water and sediment. However, the current approaches in pollutant transport modelling provide limited insights into how pollutant transfer between water and sediment phases influences their transport from the upstream towards the estuarine environment. This research study firstly identified typical patterns of metal loads along an urban river in a highly populated city in China. The outcomes were then used to conceptualise metal transfer between water and sediment phases. It was noted that physico-chemical characteristics of water and sediments play a key role in metal transfer between the two phases, and the dominant transfer path (sediment to water/water to sediment) is different between different metals, independent of their origin (crustal, anthropogenic or marine-related). Several scenarios were derived from the conceptualisation of metal behaviour. These in turn were then used to develop real-world scenarios of metal transport in rivers based on the field data. The conceptualisation of metal behaviour confirmed that each metal is likely to have a dominant phase of transport (sediment/water), which is influenced by the dominant transfer path of that metal between water and sediments. Graphical abstract: Image 1 Highlights: Each metal has a dominant transfer path (sediments to water/water to sediments). Dominant transfer path determines the dominant transport phase (sediments/water). Properties of water and sediments influence metal transfer between the phases. Metals from different origins have consistent patterns in river water and sediments.